The Correlation Between Time Management and Anxiety in Master of Education Graduate Students in XYZ University Jakarta - Kristanto, Yenny; Wijono, Silviana; Tulung, Casey Rebecca (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
There are many factors due to the increasing number of graduate students experiencing anxiety during their studies. One of the factors can be related to time management since many graduate students are students that have jobs, families, and other responsibilities. Having so much on their plate might be a cause of anxiety when it is done with poor time management on their end. Therefore, the purpose of this study is to find out whether there is a relation between time management and anxiety, and whether gender plays important role in time management among the students of Master of Education Graduate Students of XYZ University.  This research paper is a quantitative study which uses inferential statistics. The sample of this study was selected using purposive sampling technique. A total of 40 participants were recruited for this study. The data of time management were collected using a 5-point Likert scale ranging from Seldom True (1) to Very Often True (5), meanwhile for anxiety the Likert scale ranging from Not Present (1) to Very Severe (5).  The questionnaire was presented using Google Form in Bahasa then distributed through WhatsApp group. The data reliability was measured using Cronbach's Alpha with the result of 0.70. According to the survey 5 (12.5%) students had high time management, 29 (72.5%) students had moderate, and 6 (15%) students had low time management.  This study concludes that there is no correlation between time management with anxiety and the average of female students’ time management is as same as male students’ time management. In addition, regarding time management skill, it can be synthetized that most of the Master of Education Graduate Students of XYZ University are having moderate time management. Nevertheless, it is recommended that a thorough further research regarding this study should aim to investigate additional variables and factors that may contribute to the understanding of the relationship between time management and anxiety among Master of Education graduate students, so that it can have a better comprehensive evaluation in the future.